2016
DOI: 10.1007/s11906-016-0668-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on the Proximal Tubule Renin-Angiotensin System in Angiotensin II-Dependent Hypertension

Abstract: It is well recognized that the renin-angiotensin system (RAS) exists not only as circulating, paracrine (cell to cell), but also intracrine (intracellular) system. In the kidney, however, it is difficult to dissect the respective contributions of circulating RAS versus intrarenal RAS to the physiological regulation of proximal tubular Na+ reabsorption and hypertension. Here, we review recent studies to provide an update in this research field with a focus on the proximal tubular RAS in angiotensin II (ANG II)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 179 publications
(276 reference statements)
2
26
0
Order By: Relevance
“…In particular, adenosine, Ang II, NO and O2 are important modulators of arteriolar tone and reactivity, as well as tubular reabsorption (see ref. ). Numerous studies have demonstrated that oxidative stress and subsequent NO deficiency in the kidney are critically associated with development of hypertension and increased risk of adverse cardiovascular complications (see ref.…”
Section: Organ Systems Involved In the Blood Pressure Reduction By Inmentioning
confidence: 97%
“…In particular, adenosine, Ang II, NO and O2 are important modulators of arteriolar tone and reactivity, as well as tubular reabsorption (see ref. ). Numerous studies have demonstrated that oxidative stress and subsequent NO deficiency in the kidney are critically associated with development of hypertension and increased risk of adverse cardiovascular complications (see ref.…”
Section: Organ Systems Involved In the Blood Pressure Reduction By Inmentioning
confidence: 97%
“…Multiple Ga q coupled receptors have been used to probe RGS2 function in vitro such as M1 or M3 muscarinic receptors (Bodenstein et al, 2007;Gu et al, 2007Gu et al, , 2008 or the vasopressin receptor (Osei-Owusu et al, 2007). In this study, we chose the angiotensin II receptor because of its relevance in systematic regulation of vascular function and blood pressure (de Kloet et al, 2015;Cameron et al, 2016;Li and Zhuo, 2016). Moreover, RGS2 has been proposed to serve as a selective and potent regulator of AT1R due to interaction through its amino terminal domains (Heximer et al, 2003;Hercule et al, 2007;Matsuzaki et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such sophisticated autoregulation is mediated by the myogenic response and the tubuloglomerular feedback (TGF), which mainly exert their effect via modulation of afferent arteriolar tone . In addition, several hormones and endogenous substances can modulate renal autoregulation and preglomerular resistance , where adenosine, Ang II, NO and O2 have been demonstrated to be of particular importance . Abnormal renal autoregulation and altered fluid and electrolyte handling along the nephron may contribute to the development of hypertension, which in turn can induce progressive renal injuries .…”
Section: Kidneys and Renal Autoregulationmentioning
confidence: 99%